Evaluasi Promosi Penggunaan Kondom untuk Mencegah HIV/AIDS di Lokalisasi Pelacuran di Kabupaten Banyuwangi - Hafrida Ira Paramastri, Agus Priya (Berita Kedokteran Masyarakat (BKM), 2008)
Background: HIV/AIDS  in East Java  in  the year of 2005  is  the  third highest disease  in  Indonesia. The district of Banyuwangi  is  the  third  rank  in  Indonesia after Surabaya and Malang  in  terms  of  the case number. The biggest patient group of HIV/AIDS  is sexual worker women  (WPS). Various health promotion programs  in using condom have  been  implemented  although  the  case of AIDS still  tends  to  improve.Objective:  This  research was  aimed  to obtained  description  on  health promotion  program  implementation  by using condom  in  the prevention of HIV/AIDS  in  the  localization of prostitution  from  the perspective  of  those who obtained  the health  promotion and who conveyed  the  health  promotion.Method:  This was  an  emic  qualitative  research.  The main  informant was WPS which was  supported with informant  of  client, procurers,  government and NGO. The  research was  implemented  in  the  localizations  of Banyuwangi district. Data was  collected  by  using  in-depth  interview  and  observation  for  comparing  the  result of  in-depth  interview. Data was  analyzed  by  using constant  comparative method  and  data  validity was  using source  and  triangulation method.Result: The  subjects  did  not  comprehend HIV/AIDS  appropriately. Their  negotiation skill was  low  as  they were more prioritized on  the sales  result of  the sexual  relationship. The promotion media  that were sticker, poster and advertisement were not  really  interesting,  as  they were not  appropriate  for  localization.  Interpersonal  supervision by health  care provider  and  the  check up  of  reproductive  health was  not successful. Promotion  through  selling condom in parking place, condom promotion and condom ATM was able to remind the WPS to be more aware on the  transmission  of  the  disease  and  in using  condom. Media  of  film was  also  preferred.  It  is suggested  for program modification  is  by adding up  the  health promoter  from other  related   institution. Government plays  a  role in  giving  the  budget of HIV/AIDS prevention  program.Conclusion: Various  promotion media was  not  suitable with  the need  in  localization  (sticker, poster,  booklet), while other media could  influenced  to  remind  the  prevention  of HIV/AIDS  transmission  (promotion  in  parking place,  condom promotion,  supervision of  the health  care  provider). Negotiation  in  using condom was still  low. The continual  supervision  of  health  care  provider and  the promotion  in  the  parking place were expected  could be  disseminated and  continued.Keywords:  promotion evaluation,  condom, HIV/AIDS,  prostitution